The Influence of Brand Loyalty on Customers’ Repurchase Decisions of Green Beauty Product - Eristia Lidia Paramita; Ika Aprilia Saputri (Jurnal Manajemen Bisnis, 2022)
Research aims: This study examined the relationship between green beauty products and customers’ repurchase decisions. However, this study used brand loyalty as the intervening variable.Design/Methodology/Approach: This study employed purposive sampling to collect the primary data. The object of this study was The Body Shop. Questionnaires were distributed to 236 respondents aged 14-39 years old. SEM analysis was then utilized to analyze the results of the questionnaire.Research findings: The findings of this study showed that green beauty products had a significant impact on customers’ repurchase decisions. Similarly, brand loyalty has been proven to mediate the relationship between green beauty products and customers’ repurchase decisions.Theoretical contribution/Originality: The previous study has investigated the relationship between green products and customers’ repurchase decisions, but little literature involves green products in terms of the beauty industry and customers’ repurchase decisions. Another contribution is that this study revealed that it could affect the customers’ repurchase decisions on green beauty products through brand loyalty. Practitioner/Policy implication: The authors suggest that The Body Shop maintain their added value so that customers perceive more added value and do consistent purchasing in The Body Shop rather than the other brands.Research limitation/Implication: This study has limitations when developing the structural model fit. One indicator did not meet the good fit criteria: the AGFI with the marginal fit result.